Production of IgG2 Antibodies to Pneumococcal Polysaccharides After Vaccination of Treated HIV Patients May Be Augmented by IL-7Rα Signaling in ICOS+ Circulating T Follicular-Helper Cells - Abudulai, Laila N.; Fernandez, Sonia; Corscadden, Karli; Kirkham, Lea-Ann; Hunter, Michael; Post, Jeffrey J.; French, Martyn A. (Frontiers in Immunology, 2019)
Greater understanding of factors influencing the maturation of antibody responses against pneumococcal polysaccharides (PcPs) may improve pneumococcal vaccination strategies. Although PcPs are type 2 T cell-independent antigens thought not to induce follicular immune responses, we have previously shown that IgG2 antibody responses against antigens in the 23-valent unconjugated PcP vaccine (PPV23) are associated with expansion of ICOS+ circulating T follicular helper (cTFH) cells in HIV seronegative subjects but not HIV patients. As IL-7R signaling in CD4+ T cells may affect TFH cell function and is adversely affected by HIV-1 infection, we have examined the relationship of IL-7R expression on ICOS+ cTFH cells with PcP-specific IgG2 antibody responses. PPV23 vaccination was undertaken in HIV patients receiving antiretroviral therapy (n=25) and HIV seronegative subjects (n=20). IL-7R expression on ICOS+ and ICOS- cTFH cells was assessed at day(D) 0, 7 and 28. Fold increase between D0 and D28 in serum IgG1 and IgG2 antibodies to PcP serotypes 4, 6B, 9V and 14 and the frequency of IgG1+ and IgG2+ antibody secreting cells (ASCs) at D7 were also assessed. Decline in IL-7R expression on ICOS+ cTFH cells between D0 and D7 occurred in 75% of HIV seronegative subjects and 60% of HIV patients (Group A), with changes in IL-7R expression being more pronounced in HIV patients. Group A patients exhibited abnormally high IL-7R expression pre-vaccination, an association of serum IgG2, but not IgG1, antibody responses with a decline of IL-7R expression on ICOS+ cTFH cells between D0 and D7, and an association of higher IgG2+ ASCs with lower IL-7R expression on ICOS+ cTFH cells at D7. As decline of IL-7R expression on CD4+ T cells is an indicator of IL-7R signaling, our findings suggest that utilization of IL-7 by cTFH cells affects production of IgG2 antibodies to PPV23 antigens in some HIV patients.